Detection of influenza D virus in bovine respiratory disease samples, UK. Issue 5 (7th July 2019) - Dane, Hannah; Duffy, Catherine; Guelbenzu, Maria; Hause, Ben; Fee, Sean; Forster, Fiona; McMenamy, Michael J.; Lemon, Ken
Abstract: Influenza D is a newly described virus of cattle, pigs and small ruminants first detected in North America during 2011. Cattle have been shown to be the main viral reservoir and mounting evidence indicates that infection with influenza D may contribute to the development of bovine respiratory disease. The virus has been detected across the United States, Europe and Asia. To date, influenza D has not been reported in the UK. During the winter and spring of 2017/2018, we performed molecular testing of cattle submitted for post‐mortem examination where respiratory disease signs were present. We detected influenza D virus in 8.7% of cases, often as the sole viral agent and always in conjunction with bacterial co‐infection with one or more agents. Viral RNA was present in both the upper and lower respiratory tract and pathological changes in lung tissues were observed alongside signs of concurrent bacterial infections. Sequencing of one UK isolate revealed that it is similar to viruses from the Republic of Ireland and Italy.